The kinetic investigation of cationic dyes removal mechanism by using cypress cone as biomass-based adsorbent - ÖZVEREN, UĞUR (My University, 2021)
Cypress cones collected from Marmara University campus were pulverized to be used as biobased adsorption material for the studies on the removal of methylene blue (MB) dye from wastewater. During the batch adsorption studies, we examined the effects of different operating parameters on adsorption performance under the specified optimum conditions. The outcomes obtained regarding the kinetic investigation were able to explain the adsorption behavior. The adsorption kinetics in accordance with the pseudo-second order model showed that the removal mechanism of the MB dye was applicable and occurred spontaneously. In conclusion, cypress cone adsorbent can be considered as an optimal alternative source for the removal of cationic dye pollutants from wastewater due to its advantageous properties, such as porous structure, large specific surface area, and excellent adsorption efficiency (100% removal), as well as its basic and environmentally friendly nature.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)